West nile fever in the Southern federal District: an overview epizootic and epidemiological situation - S. K. Udovichenko; E. V. Putintseva; N. V. Borodai; A. V. Toporkov (Медицинский вестник Юга России, 2025)
Objective: to study the features of epizootic and epidemiological manifestations of west Nile fever (wNF) in the re gions of the Southern Federal District. Materials and methods: we used data on the registration of cases of the disease and the results of epidemiological surveillance presented in 2009–2023. Directorates of Rospotrebnadzor for the constituent entities of the Russian Federation, archival data, results of their own research, publications and dissertations. Research methods are com plex epidemiological and statistical. The sources of information were: Results: in the Astrakhan, Volgograd, Rostov regions and the Republic of Kalmykia, stable circulation of wNV in the epizootic cycle has been established, in the latter of which epizootic observation data do not correlate with low incidence. In the Krasnodar Territory, the Republics of Adygea, Crimea and the city of Sevastopol, single detections of wNV markers in zoological and entomological material do not allow assessing the intensity and extensiveness of the epizootic process. The epidemic process of wNV in the Volgograd, Astrakhan, and Rostov regions is characterized by almost annual registration of cases with increases in incidence in the interval of 1–7 years, in the Krasnodar Territory - by the outbreak nature of manifestations in some years, in other regions - by sporadic incidence. An upward trend in incidence was noted in the Krasnodar Territory and Rostov Region. The structure of morbidity is dominated by cases of infec tion among men, people aged 60 years and older, urban residents, the clinical picture is a form without damage to the central nervous system and a moderate course. Differences in the epidemiological manifestations of wNV are associated with the pecu liarities of the organization of the epidemiological surveillance system and the influence of territorial social factors. Conclusion: the results can be used in planning and conducting epizootological and epidemiological monitoring, zoning of territories, and development of management decisions.